Midlife challenges in speech perception in spatial noise under virtual reverberant environments - Harshada, Mali; Pitchaimuthu, Arivudai Nambi; Nisha, K. V. (Frontiers in Virtual Reality, 2025)
IntroductionSpeech recognition in noisy, reverberant environments is challenging, particularly with aging. Subtle spatial auditory deficits emerging in midlife may precede measurable hearing loss and impair communication. Real-world studies face challenges in control and replication, whereas virtual reality (VR) simulations offer an alternative. This study examines how age and noise location influence speech recognition in virtual reverberant environments.MethodsSixty normal-hearing adults participated: 30 young (18–40 years, M = 25.19, SD = 5.23) and 30 middle-aged (41–60 years, M = 55.79, SD = 4.57). Participants completed sentence recognition tasks in virtual acoustic simulations with three reverberation levels (anechoic, short: 0.8 s, long: 3.0 s) and three noise locations (0°, 60° right, 60° left). Sentences were presented at 0° amidst spatial noise. A generalized linear mixed model (GLMM) analyzed sentence recognition scores, with fixed effects for age, reverberation, and noise location, and random effects for participant variability.ResultsGLMM results showed middle-aged adults had poorer sentence recognition than young adults (p < 0.05). Both groups exhibited SRM in anechoic and short reverberation conditions, but middle-aged adults showed no spatial release from masking in long reverberation. Significant age-reverberation interactions indicated greater deficits in middle-aged adults under challenging acoustics.DiscussionFindings suggest that middle-aged adults may experience subtle speech perception difficulties in noisy and reverberant environments, even with clinically normal hearing. However, generalization to hearing-impaired populations remains limited.